China's engagement with the liberal international order - Chua, Ze Ping (Nanyang Technological University, 2021)
China’s re-emergence as a global power has profound implications on world politics. China has achieved tremendous economic and military power as it integrated itself into various institutions of the liberal international order. Despite being a beneficiary, China’s rise within the liberal international order contains tensions as China seeks to pursue its national interests. This paper aims to explain how China engages with the liberal international order in terms of its rules-based character and how it negotiates the United States’ dominance of the order by examining China’s behaviour and rhetorical positions in the economic and security policy areas. The paper argues that China avoids radically challenging the order’s rules by challenging them in a calibrated way to avoid being regarded as a ‘rule breaker’. In the long run, China desires to amend the order’s rules in its favour while also seeking to reduce the impact of US dominance through achieving technological independence and closer ties with neighbouring states.